Peningkatan Kualitas Produk Hukum di Kampung Wasur Melalui Pelatihan dan Pendampingan Penyusunan Produk Hukum Yang Responsif Melibatkan Gerpamat (Gerakan Partisipasi Masyarakat Adat) - Marlyn Jane Alputila; Mulyadi Alrianto Tajuddin (Universitas 45 Surabaya, 2024)
The importance of rules in the order of organizational life means that each village should have its own rules according to the specifics and potential of that village. Village regulations issued in Wasur Village sometimes do not take into account the needs or conditions of the village and do not match the level of drafting of statutory regulations such as the level of preparation, determination, implementation, assessment and reintegration of finished products. With all the problems, the resulting Village Regulations are not in accordance with the procedures for their formation.Assistance in drafting village regulations, the ultimate goal is to realize the quality and quantity of Wasur village regulations by involving the village head, village deliberation body and also facilitating gerpamat (indigenous community participation movement.The Training Program is implemented through Socialization, Training and Technical Guidance activities. Techniques for Preparing Village Regulations are implemented through Socialization and Training activities including the development of training materials, Lectures from Resource Persons, Case Studies, Brainstorming.The result of this activity is the achievement of an independent/local village that is able to make good village regulations that are in accordance with legal principles and village conditions by involving the Indigenous Community Participation Movement (Gerpamat), so that peace is guaranteed in Wasur village. The outcomes of the achievements of this activity are 1) increasing the knowledge of community members 2) publication of articles in the accredited Service Journal Sinta 3 (Jurnal of Service, 3) activities that have been carried out can be published through the Arafura News newspaper, both print and online and 1 Village Regulation legal product